Synthesis, structures, reactivity and medicinal chemistry of antitubercular benzothiazinones. Issue 32 (28th March 2023) - Seidel, Rüdiger W.; Richter, Adrian; Goddard, Richard; Imming, Peter
Abstract : Benzothiazinones are promising candidates in the fight against tuberculosis, the leading bacterial killer worldwide. We present an overview of recent developments in the field of antitubercular benzothiazinones and summarize our own contributions. Abstract : Tuberculosis is the leading bacterial killer worldwide. 8-Nitro-4 H -benzo[ e ][1, 3]thiazin-4-ones are a potent class of antitubercular agents with a new mechanism of action. BTZ043 and PBTZ169 (macozinone) have progressed to clinical studies. Herein, we give a comprehensive account of this important class of potential new drugs to treat tuberculosis. We present an overview of recent developments in the field of antitubercular benzothiazinones (BTZs) and summarize our own contributions. The review covers synthesis, structures and reactivity, mechanism of action, in vitro activity and structure activity relationships (SARs), physicochemical and pharmacokinetic properties as well as a brief summary of in vivo models and clinical studies. We address bioavailability issues and the challenge of the potentially toxic nitroaromatic moiety, including reactivity towards nucleophiles in vivo and highlight possible directions of further research into BTZs through chemical modification.